After the Dance d’Edwidge Danticat : visions carnavalesques de l’espace haïtien - Corinne Duboin (Transatlantica)
In my analysis of Edwidge Danticat’s travelogue, I will explore the Haitian American writer’s treatment of the carnivalesque in both her representation of her native land (its geography, history and culture) and her apprehension of a new self-image.